Modeling the illocutionary aspects of information-seeking dialogues - Sitter, Stefan; Stein, Adelheit (Information processing & management, 1992)
A dialogue model is presented that incorporates the illocutionary aspects of information-seeking dialogues. Directive, commissive, and assertive types of dialogue acts (e.g., asking, offering, rejecting, answering, and evaluating) are represented by a complex transition network. The model determines all legitimate types and sequences of dialogue acts and regulates the role assignments (e.g., when the information seeker and the information provider temporarily exchange their roles). Finally, an approach to integrating the illocutionary layer with other layers—which deal with thematical and rhetorical coherence—is outlined. Such an integrated model can serve as a basis for the design of human-computer dialogue systems.